Education-Job Mismatch in Azerbaijan: Exploring the Role of Social, Academic, and Individual Factors - Aghamaliyeva, Gunay (ADA University, 2023)
This study examines the relationship between educational field and job mismatch, and its potential causes in Azerbaijan, aiming to identify practical solutions to address the issue. Adopting a quantitative research methodology, the study employed a non-probability sampling method to recruit participants meeting specific criteria, including employees with higher education background residing in Azerbaijan at the time of the research. Due to the COVID-19 pandemic, a snowball sampling approach was utilized, with an online questionnaire. A total of 204 eligible respondents completed the survey, with 50 males and 154 females. The data analysis revealed a significant association between gender, education field, and job mismatch, as well as a marginal correlation between graduates’ experiences of education, and the likelihood of mismatched job occupation. These findings underscore the need for a re-evaluation of the higher education system in Azerbaijan, with a focus on aligning education and training programs with the demands of the labor market. The implications of this study extend to university students, graduates, job seekers, and employers, offering insights into early career decision-making processes in Azerbaijan.
Keywords: Higher Education system; Labor market demands; Career choice